Insertion of Telomeric Repeats at Intrachromosomal Break Sites During Primate Evolution - Nergadze, Solomon G.; Rocchi, Mariano; Azzalin, Claus M.; Mondello, Chiara; Giulotto, Elena

(untitled) (Genome Research, 2004)
Short blocks of telomeric-like DNA (Interstitial Telomeric Sequences, ITSs) are found far from chromosome ends. We addressed the question as to how such sequences arise by comparing the loci of 10 human ITSs with their genomic orthologs in 12 primate species. The ITSs did not derive from expansion of pre-existing TTAGGG units, as described for other microsatellites, but appeared suddenly during evolution. Nine insertion events were dated along the primate evolutionary tree, the dates ranging between 40 and 6 million years ago. Sequence comparisons suggest that in each case the block of (TTAGGG)n DNA arose as a result of double-strand break repair. In fact, ancestral sequences were either interrupted precisely by the tract of telomeric-like repeats or showed the typical modifications observed at double-strand break repair sites such as short deletions, addition of random sequences, or duplications. Similar conclusions were drawn from the analysis of a chimpanzee-specific ITS. We propose that telomeric sequences were inserted by the capture of a telomeric DNA fragment at the break site or by the telomerase enzyme. Our conclusions indicate that human ITSs are relics of ancient breakage rather than fragile sites themselves, as previously suggested.